Autoimmune hepatitis and pregnancy: report of two cases with different maternal outcomes - Orgul, Gokcen; Ozkan, Esra Uyanik; Celik, H. Tolga; Beksac, M. Sinan (Clinical and Experimental Hepatology, 2017)
Women of childbearing age with autoimmune hepatitis (AIH) are now able to get pregnant. The progress of the disease during pregnancy is not well clarified yet. The first pregnant woman had cirrhosis secondary to AIH, and she delivered by cesarean section. The patient had severe thrombocytopenia at the time of hospitalization. Unfortunately, she died due to massive thromboembolism at the 24th hour after delivery. The other patient had three recurrent abortions with a diagnosis of AIH. Low-dose low molecular weight heparin and low-dose acetylsalicylic acid along with low-dose prednisolone were administered during the course of the following pregnancies. The following pregnancies ended up with a living child. There is a high morbidity and mortality risk for both fetus and mother. Hepatic performance of the patients, thrombotic events, inflammatory disorders and autoimmune system activation must be the main concerns together with necessary precautions.